1994
DOI: 10.1001/jama.1994.03520060062033
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective Comparison of Mother-to-Child Transmission of HIV-1 and HIV-2 in Abidjan, Ivory Coast

Abstract: The rate of perinatal transmission of HIV-2 (1.2%) was much lower than the rate of perinatal transmission of HIV-1 (24.7%), and this was associated with more favorable survival for infants of HIV-2-infected mothers. Dually reactive women could transmit both viruses, although transmission usually involved HIV-1 only. Public health guidelines should incorporate advice that perinatal transmission of HIV-2 is rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…These data are also consistent with previous studies conducted in other West African countries that observed a higher HIV-2 frequency among individuals over 49 years and a higher HIV-1 prevalence among younger individuals [30][32]. Lower frequency of children infected by vertical transmission was observed for HIV-2 (2.3%) compared with HIV-1 (16.0%) infected individuals, as described for other countries where both types circulate [33], [34]. All HIV-2 samples belonged to the predominant group A, as previously described in Cape Verde [18] and other West African countries [35], [36].…”
Section: Discussionsupporting
confidence: 92%
“…These data are also consistent with previous studies conducted in other West African countries that observed a higher HIV-2 frequency among individuals over 49 years and a higher HIV-1 prevalence among younger individuals [30][32]. Lower frequency of children infected by vertical transmission was observed for HIV-2 (2.3%) compared with HIV-1 (16.0%) infected individuals, as described for other countries where both types circulate [33], [34]. All HIV-2 samples belonged to the predominant group A, as previously described in Cape Verde [18] and other West African countries [35], [36].…”
Section: Discussionsupporting
confidence: 92%
“…As for other epidemics driven by unprotected sex work 56,57 , commercial sex contributed markedly to HIV transmission early in the HIV epidemic. This contribution diminished with time, however, partly due to rising condom use by FSW, reflecting the importance of sustaining FSW interventions 50,58,59 .…”
Section: Discussionmentioning
confidence: 99%
“…HIV-2 is likely less prevalent due to its reduced transmissibility, which has been demonstrated for both sexual transmission and mother to child transmission [3234]. Further, HIV-2 is generally less pathogenic than HIV-1, leading to AIDS in only ~25% of untreated individuals (compared to >95% for HIV-1) [35, 36].…”
Section: Introductionmentioning
confidence: 99%